Studies of Streptococcus pneumoniae colonisation : role of capsule and induction of protective immunity - Roche, Aoife M. (Trinity College (Dublin, Ireland). Department of Microbiology, 2010)
Streptococcus pneumoniae (the pneumococcus) is a major human pathogen responsible for an estimated 1.6 million deaths each year, most of which are of young children in the developing world. Current pneumococcal vaccines target the polysaccharide capsule and despite their success in reducing invasive pneumococcal disease, there are limitations associated with their use and efficacy. These limitations, coupled with an increase in the prevalence of antibiotic resistance, have spurred research to find alternative vaccines.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin